Agricultural Wastes – A Promising Source for Biogas Production in Developing Countries of the Tropical and Subtropical Regions - Barz, Mirko (2018)
Most of the so called developing countries are located in tropical and/or sub-tropical regions whilst in contrast, most of the developed countries are in the temperate climate zones. It is expected that a huge increase in the future global energy consumption will be caused by the demand of the developing countries. Caused by the favourable climate conditions in tropical and/or sub-tropical regions the average productivity of biomass is 4 – 5 times higher than that of biomass grown in the temperate regions. Many of the developing countries today are agricultural and agro-industrial countries producing huge amounts of agricultural residues and wastes that can be used as source for energy generation. It is estimated that if only all process-based agricultural residues alone would be used, they could contribute between 25 % and 40 % of the total primary energy demand in such regions [1]. Until now, the huge amount of agricultural waste generated each year in developing countries is a headache for farmers, who are obliged to get rid of it. Open field burning and improper disposal are omnipresent in many regions and pollute the environment. Converting such waste into bioenergy such as biogas by using anaerobic digestion technologies represents an alternative treatment with a promising potential. Such treatment prevents pollution, is producing valuable and climate friendly energy and will contribute to nutrient recovery by using the digestate as fertilizer. The paper will introduce some of the most promising agricultural residues in tropical and subtropical regions which can be used as substrates or co-substrates for biogas production. Results of a research project carried out in Costa Rica will be used as a case study to show the potential of two of the major agricultural residues (pineapple and banana residues) as sources for biogas production. The opportunities and prospects for the dissemination and implementation of new and more developed technologies to improve the efficiency of the technologies will be shown.